О предпочтительных сферах применения зубчатых передач Новикова и эвольвентных - Короткин, Виктор Ильич (НТУ "ХПИ", 2016)
Дан анализ сравнительной напряжённости зубьев и нагрузочной способности зубчатых передач Новикова и эвольвентных при использовании таких резервов повышения нагрузочной способности обоих видов зацепления, как смещение исходного контура (корригирование), продольная модификация рабочей поверхности зубьев (бочкообразность) и увеличение модуля в заданных габаритах передачи. Сделаны выводы о предпочтительных сферах применения обоих типов зубчатых передач.

Comparative researches of tooth intensity of Novikov gearing and involute gearing carried out in a wide range of degrees of accuracy gears and the hardness of the teeth, as reserves for increasing the load capacity taken: a) shift of basic rack profile (correction); b) longitudinal modification of active tooth surface (barrel-shaped tooth); c) increase of the module at constant drive overall dimensions. Developed by a system of nonlinear equations and the package of computer programs, whereby the estimation of contact and bending stress state and rigidity of teeth for real gear with different hardness of the teeth surfaces. Determined, that by using these of reserves Novikov gearing are more preferred than the involute gearing for high-stressed drives relatively low rotation speeds and average degrees of accuracy: general, mining, energy, oil, metallurgical engineering industry etc. The urgent need for a the development of reliable manufacturing techniques and control of hardened Novikov gearing high degrees accuracy with ground teeth. In the absence of such technology preference should be given to hardened high-precision and adaptable to streamlined production resource involute gearing, having a favorable dynamic and vibroacoustic characteristics.
About preferred areas of Novikov gearing and involute gearing
Keywords: напряжённость; нагрузочная способность; рабочая поверхность зубьев; бочкообразность; intensity; load capacity